The Influence of Procurement of Human Resources on Work Productivity with Soft Skills and Social Relations as Intervening Variables in PDAM Tirta Silau Piasa Employees - Rosmaida Rosmaida; Syaifuddin Syaifuddin; Sofiyan Sofiyan (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
The number of employee performance that is considered not in accordance with the target causes a decrease in the quality of the company. So it takes an in-depth approach to what causes it to happen. Therefore, this study wants to test whether there is an effect of motivation and work supervision on work productivity with soft skills and social relations as intervening variables on the employees of PDAM Tirta Silau Piasa. This type of research uses causal research which aims to test hypotheses on a causal relationship between one variable and another, then determines the implications for confirmation of theoretical and empirical models built from Work Motivation and Supervision. The results of the study show that the procurement of human resources has a very large influence on the work productivity of employees at PDAM Tirta Silau Piasa. This is because with quality human resources, PDAM Tirta Silau Piasa will be more consistent in carrying out its functions. In addition, procurement of human resources will create improved performance results compared to previous results.